Produksi Cabai Rawit (Capsicum frutescens L.) pada Perbedaan Pupuk Organik Cair Melalui Drip Irigasi Otomasi dan Media Tanam - Hadi, Restu Firman; Arti, Inti Mulyo; Asnur, Paranita (Savana Cendana, 2024)
Chili pepper is one of the commodities that has economic potential. The problems that arise when cultivating chili peppers are optimal nutrient requirements and the right planting media. The purpose of this study was to determine the effect of providing various types of liquid organic fertilizers through automated drip irrigation and planting media on the production of chili peppers. The design used in this study was a Nested Design. The main plot (Factor 1) is liquid organic fertilizer with two levels, namely Superior Plant Hormone fertilizer (P1) and Herbafarm fertilizer (P2). The subplot (Factor 2) is a planting medium with four levels of treatment, namely soil planting media (control) (M0), soil planting media + rice husk charcoal + goat manure with a ratio of 1: 1: 1 (M1), soil planting media + cocopeat + chicken manure with a ratio of 3: 2: 1 (M2), soil planting media + sawdust + rice husk charcoal with a ratio of 1: 1: 1 (M3). The experiment was conducted with 4 replications so that there were 32 experimental units. The parameters observed in this study were the number of fruits per plant (fruit), fruit weight per plant (g), plant productivity (ton/ha), weight per fruit (g), fruit diameter (mm), fruit length (cm). The results showed that the provision of liquid organic fertilizer had a significant effect on fruit diameter and fruit length. while the provision of different planting media did not have a significant effect on all parameters.